KOMPETENSI PROFESIONAL DALAM PERSPEKTIF KONSELOR SEKOLAH DAN PERANANNYA TERHADAP PELAYANAN BIMBINGAN DAN KONSELING DI SMA NEGERI SE-KOTA PADANG - ., Jumail (Konselor, 2013)
Seeing to the accident happened in the field, the professional competence of school counselors was not optimal yet. It was seen that many of them were not Strata 1 (S1) of guidance and counseling. In fact, they did not have competence such as the knowledge of concept and technique in giving counseling to students. As an effect of the problem, the students did not like to share their problem to the school counselors. The purpose of the research did not only describe the professional competence in perspective of school counselors but also see the role of professional competence of school counselors against the service of guidance and counseling that was given to the student. This research used quantitative method with descriptive approaches. Next, the instruments of the research were close questionnaire and interview. The questionnaire used the model of Likert scale and for the interview, the data was analyzed to use the percentage techniqu. The result of this research explained that the professional competence of school counselors related. in middle category. Besides, the research could be a basic for the next research with focusing on one of variable.